Antonín Raymond in Japan 1948-1976 : recollections of friends - Čapková, Helena 1886-1961; Kitazawa, Koichi 1943- (Karolinum Press, 2023)
This richly illustrated publication about the post-war work of Noémi (1889–1980) and Antonín Raymond (1888–1976) presents readers with a close-up view of the world of the architects and their collaborators who rebuilt Japan upon the ruins of World War II. The recorded recollections of seven members of the Japanese Raymond studio depict the personalities of the Raymonds, comment on their work, provide an overview of the company’s daily operations and describe relationships with elite clients. Four interviews with one or more collaborators discuss the Raymonds within the context of contemporary society from different perspectives, e.g. from the point of view of a young girl or a promising architecture student. Some of the almost two hundred illustrations are published here for the first time. The material relating to the work of Noémi Raymond merits special attention, since little research has been conducted into her work up to now. Among the many projects featured, the Reader’s Digest building in Tokyo, the Gunma Prefecture Music Center or the Czechoslovak Embassy in Tokyo for example are focused on in further detail. The embassy project was very important to Antonín Raymond, and the testimony on the course of the construction and the circumstances that accompanied it from the point of view of the Japanese collaborators is unique. The book opens with Helena Čapková’s study of the pre-war activities of Raymond’s company in Japan, with a focus on maintaining contacts during the Second World War. It closes with Irena Veverková’s text about Antonín Raymond’s contacts with Czechoslovakia after 1945
Keywords: Raymond, Antonin -- 1888-1976; Raymond, Noémi P. -- 1889-1980; Geschichte 1948-1980; Architektenbüro; Architektur; Mitarbeiter; Wiederaufbau; Zeitzeuge; Japan